FTIR spectroscopic and X-ray diffraction analysis of archaeological grey potteries excavated in Alagankulam, Tamil nadu, India - G. Velraj2, P. Sathya1* and (Journal of Experimental Sciences, 2011)
Archaic potteries are the representative tool for material culture that results the interaction between man and his territory. They also allow us to reconstruct the whole manufacturing process from the preparation of the paste to the firing of artifacts. Each of the pottery production reveals us the potterÃ¢â‚¬â„¢s technical skills, their artistic sense and their practical necessities. In this regard, scientific analyses applied to pottery give the possibility of evaluating the ceramic raw materials and of the clay type. X-ray diffraction and Fourier Transform Infrared Spectroscopic analysis of grey pottery fragments from an intensively studied Alagankulam archaeological site, Ramanathapuram district, Tamilnadu, India belonging to first century BCE is detailed in this work. By knowing the crystalline phase and chemical composition of minerals present in the pottery sherds through the XRD and FT-IR respectively we tried to determine the materials used by the potters, and the clay origin. We also examined the changes of phases produced by the heating which could furnish information on the manufacturing conditions. Hence, both of these methods enables usÃ‚Â  to reveal differences in the mineralogy of a components, and characteristic minerals as Ã¢â‚¬Å“fingerprintsÃ¢â‚¬Â which may allow distinguishing potteries of different provenance and origin.